Three Regularization Methods for A Homogeneous Time Fractional Diffusion Equation with Space - Dependent Diffusivity Coefficient - Quang Huy, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 40 No 2DO - 10.25073/2588-1124/vnumap.4898, 2024)
We studied an inverse problem for a time fractional diffusion equation with space - dependent diffusivity coefficient in the nonhomogeneous case. This problem is ill – posed in Hadamard’s sense.  So, a regularization is essential. Using three regularization methods, we get the estimation of the error between the regularized solution and the exact solution